Model Test Ultimate Bearing Capacity of Bakau Piles Foundation on Soft Soil Deposit - Muhammad o Yunus (EPI International Journal of Engineering, 2018)
The pile foundation is one of the deep foundation types commonly used to support building loads when hard soil layers are deeply located. To determine the ultimate bearing capacity of a pile foundation of the load test results, there are several methods commonly used to interpretation test results such as Davisson method, Mazurkiewich method, Chin method, Buttler Hoy method and De Beer method. The aim of this study was to determine the characteristics of soft soil and bakau piles used in the study and to analyze the size of the bearing capacity ultimate of pile foundation that is modeled on a small scale in the laboratory. From the test results of material characteristics of the soil used is organic clay type with medium plasticity with specific gravity 2.75, liquid limit, LL = 50.36% and plasticity index, PI = 13.2%. While the results of testing the characteristics of bakau piles obtained average water content of 21.58%, tensile strength of 18.51 MPa, compressive strength of parallel fiber 23.75 MPa and perpendicular fiber 14.10 MPa, bending strength 106, 22 MPa, and strong split 29.91 MPa. From the result of loading test of the foundation model in the laboratory, it is found that the ultimate bearing capacity of the model without foundation is 41.00 kN with the ultimate settlement of 14.00 mm, the model of the 20 cm long bakau piles foundation is 52.00 kN with the ultimate settlement of 13.00 mm, the foundation model a 30 cm long bakau piles foundation of 54.00 kN with a 10.00 mm ultimate settlement, a 40 cm long bakau piles foundation model of 56.00 kN with an ultimate settlement of 8.50 mm.